The Association between Mental Health and Stressful Life Events among Undergraduate Students in Cyprus: A Descriptive Correlational Study - Sokratous, Sokratis; Alexandrou, George; Zavrou, Rafailia; Rousou, Elena; Sokratous, Nikolas; Karanikola, Maria (My University, 2025)
Background: Previous studies have indicated a causal link between stressful life experiences and mental health. However, little is known about the impact of the frequency and seriousness of recent stressful life events on clinical mental discomfort among university students. This study explored the mental health status of undergraduate students in Cyprus. It examined the association between the number and severity of stressful life events and clinical symptoms of mental distress. Methods: This was a cross-sectional, descriptive, correlational study conducted using convenience sampling, with a total of 1,500 undergraduate students participating. Descriptive statistics for sociodemographic characteristics, mental distress symptoms, and life events of the participants were calculated and expressed in frequencies, mean values, and standard deviations. One-way analysis of variance and independent sample t-tests were conducted to compare the General Health Questionnaire – 28 (GHQ-28) subscales with groups based on the number of events and total score in Life Events Scale for Students (LESS). Results: After adjusting for sociodemographic characteristics using logistic regression analysis, gender remained the only variable significantly associated with mental distress symptoms before and after controlling for stressful life events, with women being 1.6 times more likely to report clinical levels of distress than men (95% CI: 0.98–2.46). However, a statistically significant association was observed between gender and mental distress symptoms. Specifically, women had a higher level of mental distress than men. Conclusion: Individual characteristics, stress, negative life events, and psychological distress were interconnected. Collaboration among teachers, students, parents, and mental health professionals is essential to create a supportive and nurturing school environment.
Keywords: Stressful Life Events; Life Events Scale for Students; General Health Questionnaire – 28 scale; University Student